EFFECTIVENESS OF SLOW DEEP BREATHING WITH ZIKIR TO DECREASING OF BLOOD PRESSURE AND IMPROVING SLEEP QUALITY IN PATIENTS WITH HYPERTENSION IN THE WORKING AREA OF GODEAN 1 PUBLIC HEALTH CENTRE OF YOGYAKARTA - Niken Setyaningrum; Suib Suib (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Hypertension is one of the deadliest diseases in the world and is currently listed as the third killer disease after heart disease and cancer. Treatment of hypertension requires a long time and requires a lot of money. Therefore, it is necessary to consider using a non-pharmacological approach that is natural to control high blood pressure and improve sleep quality. Hypertension can be controlled with non-pharmacological therapy using slow deep breathing relaxation techniques combined with zikir. Objective of this study is to determine the effectiveness of slow deep breathing with zikir of decreasing blood pressure and improving sleep quality. This study uses Quasi experimental with Comparison Group. Sampling using purposive sampling. The sample size in this study were 30 respondents with a sample of 15 respondents in the intervention group and control group. The intervention group will get a slow deep breathing treatment with remembrance while the control group will only get slow deep breathing treatment. Intervention for 14 days Measurements taken were measuring blood pressure using a sphygmomanometer and a stethoscope, while for sleep quality using the Pittburgh Sleep Quality Index (PSQI) questionnaire. Analysis used by Mann Whitney for blood pressure and Independent sample t test for sleep quality. After the intervention is given there is a decrease in blood pressure and an improving in sleep quality. Non-pharmacological intervention of slow deep breathing with zikir is more effective for decreasing blood pressure and improving sleep quality in patients with hypertension. The results of this study can be applied as non-pharmacological therapy in hypertensive patients and additional teaching materials for nursing care in hypertension.